1972
DOI: 10.1136/bjo.56.5.425
|View full text |Cite
|
Sign up to set email alerts
|

Scleral gel contact lenses in treatment of dry eyes.

Abstract: In the past I5 years various types of scleral contact lenses have been developed for the treatment of pathological conditions of the cornea and conjunctiva. Our previous investigations found the hydrophilic corneo-scleral lens very effective in the treatment of various inflammatory and degenerative corneal changes (Krejci, I970, 1971).In our present study the Czech hydrophilic corneo-scleral contact lens (Spofa lens) has been employed in the treatment of dry eye caused by various conditions such as keratoconju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Since it is accepted that SS is a chronic benign inflammatory disease characterized by remissions and exacerbations, the results of this study have been withheld until several years have elapsed. For this reason also we make no attempt to comment on forms of treatment such as hydrophilic contact lenses (Gasset and Kaufman, 1971;Krejci, 1972) or motorized fluid delivery from reservoir glasses (Dohlman, I97I) which as yet we have not utilized in a large series of patients.Since there is at present nothing that will eradicate KCS in Sj0gren's syndrome, our aim has been to produce reliefofsymptoms, reduction in signs, and thus a reduced incidence of irreversible ocular damage over a long period of time.Patients studied 98 patients suffering from KCS were supervised for no less than 5 years. All were suffering from definite rheumatoid arthritis according to the American Rheumatism Association criteria (Ropes, Bennett, Cobb, Jacox, and Jessar, 1959).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is accepted that SS is a chronic benign inflammatory disease characterized by remissions and exacerbations, the results of this study have been withheld until several years have elapsed. For this reason also we make no attempt to comment on forms of treatment such as hydrophilic contact lenses (Gasset and Kaufman, 1971;Krejci, 1972) or motorized fluid delivery from reservoir glasses (Dohlman, I97I) which as yet we have not utilized in a large series of patients.Since there is at present nothing that will eradicate KCS in Sj0gren's syndrome, our aim has been to produce reliefofsymptoms, reduction in signs, and thus a reduced incidence of irreversible ocular damage over a long period of time.Patients studied 98 patients suffering from KCS were supervised for no less than 5 years. All were suffering from definite rheumatoid arthritis according to the American Rheumatism Association criteria (Ropes, Bennett, Cobb, Jacox, and Jessar, 1959).…”
mentioning
confidence: 99%
“…Since it is accepted that SS is a chronic benign inflammatory disease characterized by remissions and exacerbations, the results of this study have been withheld until several years have elapsed. For this reason also we make no attempt to comment on forms of treatment such as hydrophilic contact lenses (Gasset and Kaufman, 1971;Krejci, 1972) or motorized fluid delivery from reservoir glasses (Dohlman, I97I) which as yet we have not utilized in a large series of patients.…”
mentioning
confidence: 99%
“…Most studies regarding scleral lenses and their potential benefits in the management of the ocular sequalae of Sjøgren syndrome are case series or cohort designs. Even though there are some reports from as early as the 1970's reporting on the benefit of scleral lenses for the treatment and management of dry eye disease [67,259,260], none specifically report on the benefits of dry eye signs and symptoms associated with Sjøgren syndrome. In 1992, a case series reported on the use of scleral lenses for ocular surface disease and dry eye [73].…”
Section: Sjøgren Syndromementioning
confidence: 99%
“…Based on the evidence found in the literature, SJS patients benefit more from scleral lenses than other contact lens options. These benefits have been reported as early as the late 1960s in case reports [260,274,275]. A study from 1966 reported on the successful outcome of flush-fitting scleral lenses (moulded lenses that conform to the cornea and sclera) [274], which was soon followed by reports of SJS patients managed with this same type of scleral lens design and fitting approach [67,275].…”
Section: Stevens-johnson Syndrome (Sjs)mentioning
confidence: 99%
“…Rigid gas-permeable scleral lenses have been used successfully in the treatment of severe dry eye for years. [145][146][147] Widespread use of scleral lenses 148 may be limited by fitting difficulties (particularly in the presence of conjunctival cicatrization), patient willingness and ability to wear the lenses, and high costs. Soft contact lenses may provide symptomatic relief in selected cases, particularly in the setting of filamentary keratitis.…”
Section: Severe Dry Eyementioning
confidence: 99%